Feminist Discussions in Brahui Poetry: A Research Review - Shah, Faiza Ali; Baloch, Manzoor (sourcecoder, 2025)
Feminism is a movement that originated in the West, aimed at fighting against the oppression and exploitation faced by women in society and advocating for their rights and issues. In the Brahui society, which is known for its conservative nature, women are still exploited under the name of Suryat (a social practice), and are subjected to blood money. If a woman dares to assert herself by choosing her life partner, she is condemned as immoral and silenced. Poetry, which is often regarded as the voice of revolution, depicts the highs and lows of society, attempting to reform it. However, the majority of Brahui poets have shown criminal neglect in addressing these matters. Even in this modern age, their poetry remains focused on the beauty of nature, the features and charms of the beloved, and the delicate nuances of romanticism. In Brahui society, the attitude towards women, under the guise of customs and traditions, has never been openly criticized in poetry or prose. Among Brahui poets, Professor Tahira Ehsaas Jattak and Afzal Murad are two poets who have openly or subtly, through hints and allusions, addressed feminist themes in their work.